2020
DOI: 10.1101/2020.06.25.20139782
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An Epidemic Model SIPHERD and its application for prediction of the spread of COVID-19 infection in India

Abstract: After originating from Wuhan, China, in late 2019, with a gradual spread in the last few months, COVID-19 has become a pandemic crossing 9 million confirmed positive cases and 450 thousand deaths. India is not only an overpopulated country but has a high population density as well, and at present, a high-risk nation where COVID-19 infection can go out of control. In this paper, we employ a compartmental epidemic model SIPHERD for COVID-19 and predict the total number of confirmed, active and death cases, an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…The extent of lockdown and capacity of mass testing also influenced the effectiveness of these interventions on flattening the incidence and mortality curve, as illustrated by Mahajan et al . 30 This study showed that with the same number of tests per day, the stricter the lockdown is, the greater the reduction of confirmed, active, and total death cases. This study also illustrated that with the same level of lockdown, the higher the daily number of tests done per day (8,000 vs 4,000 increase of tests per day, saturated at 300,000 and 200,000 tests/ day respectively) would result in lower number of confirmed, active, and total death cases.…”
Section: Discussionmentioning
confidence: 73%
“…The extent of lockdown and capacity of mass testing also influenced the effectiveness of these interventions on flattening the incidence and mortality curve, as illustrated by Mahajan et al . 30 This study showed that with the same number of tests per day, the stricter the lockdown is, the greater the reduction of confirmed, active, and total death cases. This study also illustrated that with the same level of lockdown, the higher the daily number of tests done per day (8,000 vs 4,000 increase of tests per day, saturated at 300,000 and 200,000 tests/ day respectively) would result in lower number of confirmed, active, and total death cases.…”
Section: Discussionmentioning
confidence: 73%
“…Since no validations have been performed in this context before, there is no pre-specified acceptable range of accuracy for this validation. However, accuracy of the model in most of the cases is within the accepted accuracy range of some other related research models [ 77 , 78 ]. Therefore, the results successfully confirm the mathematical model.…”
Section: Resultsmentioning
confidence: 91%
“…Other different methods can be found in literature with similar objectives, some above mentioned. For example, a mathematical model named SIPHERD has also been used to predict the total number of confirmed, active and death cases in India [44] . Also focusing on the country level, other authors propose the ARIMA prediction model to forecast the expected daily number of COVID-19 cases in Saudi Arabia for the next four weeks, from the collected data of almost two months in the country [45] .…”
Section: Related Workmentioning
confidence: 99%